Evaluation on the Implementation of Maternal and Child Health Service Reporting by Coordinator Midwives at Primary Healthcare Centers in Nabire District, Papua Province - Yokbeth Kareth; Cahya Tri Purnami; Ayun Sriatmi (Jurnal Manajemen Kesehatan Indonesia, 2015)
Pencatatan data pelayanan KIA di Dinas Kesehatan Kabupaten nabire tidak lengkap karena data dari puskesmas  tidak masuk tepat waktu. Disisi lain, hasil PWS digunakan untuk perencanaan program KIA dalam rangkan penurunan AKI. Tujuan penelitian adalah menjelaskan pelaksanaan pencatatan data pelayanan KIA dan pelaporannya oleh Bidan Koordinator di puskesmas Distrik Nabire. Penelitian menggunakan metode kualitatif. Informan utama bidan koordinator dan informan triangulasi bidan desa, kepala puskesmas dan Kasie KIA DKK. Pengumpulan data dengan wawancara mendalam dan dianalisis dengan content analysis. Hasil penelitian menunjukkan bahwa puskesmas yang pencatatan & pelaporan KIA baik, bidan koordinatornya melakukan pencatatan lengkap dan mengumpulkan tepat waktu setiap tanggal 10 ke DKK. Bidan telah mendapat pelatihan khusus tentang pencatatan & pelaporan KIA. Pada puskesmas yang pencatatan & pelaporan KIA kurang baik, bikor tidak mengisi kolom-kolom isian format secara lengkap dan tidak mengerti cara mengisi format isian yang sering berubah. Bidan belum mendapat pelatihan khusus. Keberhasilan dalam kelengkapan pencatatan & ketepatan pelaporan dipengaruhi oleh kelengkapan dan ketepatan pelaporan bidan pustu ke puskesmas. Keterlambatan disebabkan oleh jarak dan akses geografis yang sulit terjangkau serta beban kerja yang berat. Semua bikor mempunyai sikap dan motivasi baik. Supervisi Kepala Puskesmas yang pencatatan & pelaporan KIAnya baik dilakukan sebulan sekali dan yang kurang baik 3 bulan sekali. Supervisi DKK ke puskesmas yang baik 3 bulan sekali dan puskesmas yang kurang baik 6 bulan sekali. Disarankan agar DKK mengalokasikan anggaran untuk pelatihan khusus pencatatan & pelaporan KIA bagi bikor yang belum dilatih serta mengusahakan melengkapi sarana prasarana terutama di puskesmas dengan akses yang sulit.  Recording of KIA (maternal and children health) data in Nabire district health office (DKK) was not complete because data from primary healthcare centers (puskesmas) did not arrive at DKK Nabire on time. On the other side, results of PWS (local monitoring area) were used for KIA program planning in order to reduce AKI (maternal mortality rate). Objective of this study was to explain the implementation of recording and reporting KIA service data by coordinator midwives in puskesmas of Nabire district. This was a qualitative study. Main informant was coordinator midwives, and triangulation informants were village midwives, heads of puskesmas, and heads of KIA section of DKK. Data were collected through in depth interview. Content analysis method was applied in the data analysis.Results of the study showed that in the puskesmas with good KIA recording and reporting, coordinator midwives did complete recording and reporting and submit them on time, every 10 th day of the month, to the district health office; midwives had received special training regarding KIA recording and reporting. In the puskesmas with inadequate KIA reporting and recording, coordinator midwives did not fill the provided coulombs in the forms completely, and they did not know how to fill the forms that were changed frequently; midwives had not received special training. Successfulness in completion of recording and reporting punctuality was influenced by completeness and punctuality of reporting by midwives in the subsidiary primary healthcare center to the main primary healthcare center. The delay was caused by distance and difficult geographical accessibility, and heavy workload. All coordinator midwives had good attitude and motivation. Supervision by head of puskesmas with good KIA recording and reporting was done every month, and for the puskesmas with inadequate KIA recording and reporting was done every 3 months. Supervision by DKK to puskesmas with good KIA recording and reporting was done every 3 months, and to puskesmas with inadequate KIA recording and reporting was done every 6 months.Suggestions for DKK are to allocate budget for special training in KIA recording and reporting for coordinator midwives who have not received training, and to complete facilities especially in puskesmas with difficult accessibility.